Acute-phase plasma proteomics of rabbit lung VX2 tumors treated by image-guided microwave ablation - Cheng, Lin; Peng, Jin-zhao; Li, Sheng-wei; Bie, Zhi-xin (Frontiers in Oncology, 2024)
PurposeTo explore the plasma proteomic changes of rabbit lung VX2 tumors treated by microwave ablation, and to explore the molecular pathway mechanisms that may be involved.MethodsNew Zealand white rabbits were inoculated with VX2 tumor cell suspension in the right lower lung and treated with microwave ablation after 2-3 weeks of tumor formation. Blood was collected at 5 time points (TP1 TP5) before and after ablation by cardiac blood sampling and pre-treated before proteomic analysis. The plasma proteome was analyzed by Data-Independent Acquisition (DIA).ResultsDifferent molecular pathways were activated at different time points:(i) TP1vsTP2: more proteins were down-regulated and enrichment analysis showed that the proteasome pathway was activated. The abnormal protein folding process involved in this pathway is closely related to the process of tumor development. (ii) TP2vsTP3: more proteins were up-regulated although the number of differentially differentiated proteins was lower and enrichment analysis showed that the phagosome pathway was activated. After microwave ablation inactivates tumor cells, it activates the phagosomal pathway for immune clearance of necrotic tumor tissue. (iii) TP3vsTP4: more down-regulated proteins, enrichment analysis showed that cysteine and methionine metabolism pathway was activated. Decreased metabolism of these amino acids suggests that cancer progression may be blocked after microwave ablation therapy. (iv) TP4vsTP5: the number of differential proteins was less and more down-regulated proteins, enrichment analysis showed that glutathione metabolism and metabolism of xenobiotics by cytochrome P450 pathway were activated. The down-regulated proteins in this pathway may suggest that microwave ablation may have reduced resistance to certain chemotherapeutic agents following.ConclusionsIn the process of lung cancer treatment by microwave ablation, the changes of proteins on the possible molecular pathways at each time point are related to lung cancer, and not only involve some simple inflammatory reactions, and some of the proteins released by destroying the tumor cells can be used as possible drug binding sites and reduce drug resistance.